Clinicopathological Evaluation of Meningiomas: Experience from a Tertiary Care Hospital - Patel , Jigna Prakashbhai; Jansari, Trupti Rajeshbhai; Thorat, Rutik (Research Highlights in Disease and Health Research Vol. 7, 2023)
The present study highlights the incidence, anatomical location, sex and age Predilection, histological variants and grading of meningiomas based on WHO 2016 classification to correlate clinical features and radiological findings with those of histopathological findings. Meningiomas are the most common non-glial tumours of the central nervous system, accounting for between 16 and 20% of all intracranial tumours. This grading helps in predicting their behaviour and deciding treatment strategy. Meningiomas comprise 15%–20% of all primary intracranial tumors. They are twice as common in females as compared to the male population, but a reverse male-to-female preponderance of 3:1 has been reported in the malignant form. The incidence increases with age with peak incidence between the ages of 40 and 60 years. A slight drop after the 8th decade has been noted. They are generally benign tumors, and most patients are cured after surgery and remain free of recurrence. This case series was conducted at Dhiraj Hospital and Shrimati Bhikiben Kanjibhai Shah Medical Institute & Research Centre, Sumandeep Vidyapeeth. The biopsy specimens of all the enrolled patients (diagnosed with meningioma by the neurosurgeons and radiologists) sent to our department over a period of November 2016 to July 2018 were included. Total 30 meningioma tumors were included in the study. Most of them were intracranial, predominantly involving the posterior fossa of brain, females and the 41 – 60 age group. The most common histological subtype was psammomatous followed by meningothelial. Majority (93.33%) were benign grade I tumors. In 90% cases radiological diagnosis matched exactly with the histopathological diagnosis. Aggressive behaviour and a high risk of recurrence are associated with a small number of histological features and variants. To increase accuracy and reproducibility, it is crucial to grade and diagnose these tumours histopathologically accurately.